2017
DOI: 10.1002/jcb.26363
|View full text |Cite
|
Sign up to set email alerts
|

Anoikis resistance and oncoviruses

Abstract: Anoikis is known as a special type of programmed cell death which occurs in response to loss of correct cell-extracellular matrix (ECM) connections. This process could be as pivotal event in normal development and tissue homeostasis and found as important mechanism in cancer invasiveness and metastasis. The persistent infection with oncoviruses including EBV (Epstein Bar virus), HPV (Human Papillomaviruses), HBV (Hepatitis B virus), KSHV (Human herpesvirus 8), HTLV-1 (Human T-lymphotropic virus-1), and HCV (He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 77 publications
1
54
0
Order By: Relevance
“…It has been reported that the LMP1 down-regulates the E-cadherin expression and up-regulates TWIST and other transcription factors linked to the cell motility [69,70]. The EBV-protein, LMP-1, leads to anoikis resistance by inducing the expression of anti-apoptosis proteins survivin, CD44, the inhibitor of DNA binding 1 (Id1), Bim and ROS [63,71]. Moreover, the co-expression of E6 and LMP1 triggers some processes, including tumor-formation ability, anchorage-independent growth, resistance to apoptosis and cell proliferation, in nude mice when comparing with the expression of E6 or EBNA1 alone [72].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the LMP1 down-regulates the E-cadherin expression and up-regulates TWIST and other transcription factors linked to the cell motility [69,70]. The EBV-protein, LMP-1, leads to anoikis resistance by inducing the expression of anti-apoptosis proteins survivin, CD44, the inhibitor of DNA binding 1 (Id1), Bim and ROS [63,71]. Moreover, the co-expression of E6 and LMP1 triggers some processes, including tumor-formation ability, anchorage-independent growth, resistance to apoptosis and cell proliferation, in nude mice when comparing with the expression of E6 or EBNA1 alone [72].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, anoikis is known as a physiologic process that is involved in removing of the detachment cells. Inhibition of anoikis is one of the important mechanisms in cancer invasiveness and metastasis that can be performed by viruses (Kakavandi et al, ). We found that the expression levels of LMP‐1, LMP‐2A, and EBERs were higher in tumor tissue and the EBV‐positive group compared with healthy tissues and the EBV‐negative group (Table and Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…However, scientific evidence linking viral infections to tumor development has increased ( 296 ). Currently, between 15% and 20% of neoplasms are considered to be related to primary viral infections ( 297 ). These oncogenic viruses integrate into the host cell genome and utilize host signaling pathways to regulate cell proliferation and differentiation, genomic stability, apoptosis, and immune system recognition ( 298 , 299 ).…”
Section: Autophagy During Viral Infectionmentioning
confidence: 99%